PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ULAR TANGGA MATA PELAJARAN IPAS SISWA KELAS IV SDN 01 KOTO BARU - Muhammad Subhan; DwiNovri Asmara; Ice Yurlinda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to develop snake and ladder media in the science and science subject on the material Changing the Form of Energy in grade IV of SDN 01 Koto baru. Because the results of observations and interviews with class IV homeroom teachers found low student interest in learning in the classroom, the existence of snake and ladder media can help increase the interest andincrease the interest and learning outcomes of students with a total of 28 students. The researcher developed this study using the stages of the Research and Development (R&D) method in the ADDIE model which has 5 stages, namely: 1. The stage of analyzing needs, needs, characteristics of students, and curriculum (Analyze), 2. Learning planning stage (Design), 3. The development stage is to develop a snake and ladder product by testing the validity in the form of a questionnaire (Development). The researcher obtained the percentage of the final product score from the two validators with an average of 82% in the Very Valid category, 4. The implementation stage conducts a practicality test, product effectiveness to educators and students with an educator response questionnaire and a student response questionnaire with a percentage value of 89% in the Very Practical (Implementation) category, 5. The evaluation stage is the stage of knowing the revisions made in the product to develop learning from all previous stages (Evaluation).